TEAD1 is crucial for developmental myelination, Remak bundles, and functional regeneration of peripheral nerves - Grove, Matthew; Kim, Hyukmin; Pang, Shuhuan; Amaya, Jose Paz; Hu, Guoqing; Zhou, Jiliang; Lemay, Michel; Son, Young-Jin (eLife, 2024)
Previously we showed that the hippo pathway transcriptional effectors, YAP and TAZ, are essential for Schwann cells (SCs) to develop, maintain and regenerate myelin . Although TEAD1 has been implicated as a partner transcription factor, the mechanisms by which it mediates YAP/TAZ regulation of SC myelination are unclear. Here, using conditional and inducible knockout mice, we show that TEAD1 is crucial for SCs to develop and regenerate myelin. It promotes myelination by both positively and negatively regulating SC proliferation, enabling Krox20/Egr2 to upregulate myelin proteins, and upregulating the cholesterol biosynthetic enzymes FDPS and IDI1. We also show stage-dependent redundancy of TEAD1 and that non-myelinating SCs have a unique requirement for TEAD1 to enwrap nociceptive axons in Remak bundles. Our findings establish TEAD1 as a major partner of YAP/TAZ in developmental myelination and functional nerve regeneration and as a novel transcription factor regulating Remak bundle integrity.
Keywords: Schwann cells; myelination; yap; peripheral neuropathy; taz; remak